Two novel heterozygote mutations of ATM in a Chinese family with dystonia-dominant ataxia telangiectasia and literature review - Liu, Zhi-Jun; Wang, Ya-Ling; Xu, Yan (Frontiers in Pediatrics, 2023)
Ataxia-telangiectasia (A-T) is an autosomal recessive disorder with high clinical heterogeneity. A-T may present in complicated variable forms, including classic A-T and milder form of AT. Contrary to the classic A-T, the milder form does not present the cardinal features of A-T such as ataxia and telangiectasia. A few ATM mutations have been reported in variant A-T cases manifesting isolated generalized or segmental dystonia without any signs of classical A-T. To date, more than 400 ATM -related mutations have been identified. In this study, target exome-sequencing was performed in an A-T pedigree with predominant dystonia. Two novel ATM mutations, p.I2683T and p.S2860P, were identified in the family. We then reviewed previously published literatures of genetically confirmed A-T cases with predominant dystonia and summarized the clinical characteristics of dystonia-dominant A-T. To our knowledge, this is the first report of A-T patient with predominant dystonia in China. Dystonia may appear as one of the predominant manifestations or initial symptom of A-T. Early ATM genetic testing should be considered for those patients with predominant dystonia, despite without accompanying ataxia or telangiectasia.